Contribuição ao estudo do efeito do uso de aditivos incorporadores de ar no avanço da frente de carbonatação em compósitos de matriz cimentícia - Evando de Lacerda (2016)
The carbonation process is one of the causes of hydrogenionic potential (pH) reduction in cementitious composites. In the case of reinforced concrete structures, the loss of alkalinity can lead to depassivation of reinforcement, giving conditions to start a corrosion process. In this work, the effects of the air-entraining additives were evaluated in specimens prepared from three distinct cement matrix mortar mixes, the forward the speed of carbonation and the changes in void structure of the material. For this, the progress of carbonation front was monitored using a phenolphthalein solution, prepared according to the standards of European Standard EN 14630: 2006, at the same time to the measurement of pH variation on the surface of the composite, using specific equipment for this purpose. Cylindrical samples were used in dimensions of (2 x 4) cm and (5 x 10) cm, which were maintained in a carbonation chamber under controlled conditions of humidity, temperature and CO2 concentration. To assess the changes in pore microstructure of the cement matrix material, a specimen in size of (2 x 4) cm, from each of the three mixes studied, has been tested at 0 and 14 days of accelerated carbonation, using techniques of X-ray microtomography, mercury and helium pycnometry. It has been shown that the use of the pH reading device allows an efficient monitoring of pH variation as a function of carbonation time, making it possible to detect alkalinity reduction in regions not indicated by the phenolphthalein, because the pH values were above the turning range of phenolphthalein solution. From the -CT, it was possible to analyze the percentage of pores present in the material matrix and the connectivity between them, but it did not allow showing the densification of material present in the outermost layer of the specimen. The results obtained by mercury and helium pycnometry showed a direct relation between pore volume found for each studied mixes and the forward speed of the carbonation front.